Studi Eksploratif Persepsi dan Etika Masyarat Jawa dalam Menghadapi Erupsi Gunung Semeru - Ary Purwantiningsih; Sidik Puryanto; Dwi Riyanti (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2023)
This study aims to explore the ethical perceptions of the Javanese community in dealing with the eruption of Mount Semeru in Lumajang, East Java. This type of research is qualitative, using exploratory methods. Exploration was carried out with 30 informants who were divided into 4 groups, namely general public groups, indigenous peoples groups, santri community groups, and modern community groups, but in this study 3 groups were crucial to determine the research results. The results of this study show differences in the perceptions of the three groups, namely indigenous groups using a mythical approach, santri community groups using religious and scientific approaches, while modern community groups use a scientific approach. However, there are some modern people who still believe and believe in myths. The conclusion of this study is that the differences in the perceptions of the three groups represent the way of arguing with their beliefs and beliefs.